Leadership capabilities of physiotherapy leaders in Ireland: Part 2. Clinical specialists and advanced physiotherapy practitioners. (2nd November 2019) - McGowan, E.; Elliott, N.; Stokes, E.
ABSTRACT: Background : Investigation of the leadership capabilities of physiotherapy managers found that they report predominantly demonstrating capabilities associated with the human resource and structural frames. However, little is known about the leadership capabilities of clinical specialists and advanced physiotherapy practitioners (APPs) who also are identified as having responsibility for leadership. Objective : To explore clinical specialists´ and APPs' perceptions of their leadership capabilities and compare them with the reported leadership capabilities of physiotherapy managers. Methods : Semi-structured interviews were conducted with a purposive sample of 17 physiotherapy clinical specialists and APPs from a range of practice settings across Ireland. The interviews were analyzed using template analysis and the coding template was based on the Bolman and Deal Leadership framework. Results : The participants described demonstrating leadership capabilities associated with each of the four leadership frames. However, the language used by the clinical specialists/APPs suggested that they work predominantly through the human resource frame. Structural frame capabilities were reported by the clinical specialists/APPs and there were some differences to those reported by the managers. In keeping with the reported leadership capabilities of the physiotherapy managers, the employment of capabilities associated with the political frame varied between participants and symbolic frame capabilities were underused. Conclusion : There are many similarities in the self-reported leadership capabilities of managers and clinical specialists/APPs. However, differences were also noted. Both cohorts of physiotherapy leaders may benefit from specific development programs to develop leadership capabilities associated with the political and symbolic frames.